Peningkatan Kemampuan Menulis Teks Prosedur Melalui Metode Demonstrasi Pada Siswa Kelas XI SMAN 1 Indrapuri - Fadhilah, Nurul; Yulizar, Meri; Almunadia, Wina (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The study aims to determine the increase in students' ability to write procedural texts using the demonstration method. Writing is closely related to students because writing is one of the results of students in learning and the learning process. The study used class action research conducted on class XI students of SMAN 1 Indrapuri. Data were collected through observation, interviews, and tests. The results of the study showed that: (1) the demonstration method can improve the quality of the process of learning to write procedural texts marked by increased student activity, teacher skills, and student learning outcomes. The distribution of the data obtained shows that the ability to write procedural texts with demonstration learning methods obtains an average value of 67.12. The average value obtained is still below the specified standard, which is 70. Then, cycle II is carried out again by adding treatments. Students wrote procedure texts by applying the demonstration learning method and obtained an average value of 75.68. This proves that the demonstration learning method has a significant effect on the ability to write procedural texts for class XI students of SMAN 1 Indrapuri